2007
DOI: 10.1007/s11664-007-0245-y
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Characterization of Defects Introduced During Sputter Deposition of Schottky Contacts on n-type Ge

Abstract: The authors have investigated by deep level transient spectroscopy the electron traps introduced in n-type Ge during sputter deposition of Au Schottky contacts. They have compared the properties of these defects with those introduced in the same material during high-energy electron irradiation. They found that sputter deposition introduces several electrically active defects near the surface of Ge. All these defects have also been observed after highenergy electron irradiation. However, the main defect introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
(24 reference statements)
0
12
1
Order By: Relevance
“…We also show that the concentrations of the most prominent EBDinduced defect, the V-Sb centre, depended on the metal deposited by EBD via the melting point of the metal and the influence thereof on the vacuum during metallization. We have found that sputter deposition also introduces several electrically active defects near the surface of Ge, but, contrary to what has been reported elsewhere [9], it did not introduce the V-Sb centre in our experiments. Most of the defects introduced by EBD and sputter deposition have also been observed after high-energy electron irradiation.…”
Section: Introductioncontrasting
confidence: 99%
See 3 more Smart Citations
“…We also show that the concentrations of the most prominent EBDinduced defect, the V-Sb centre, depended on the metal deposited by EBD via the melting point of the metal and the influence thereof on the vacuum during metallization. We have found that sputter deposition also introduces several electrically active defects near the surface of Ge, but, contrary to what has been reported elsewhere [9], it did not introduce the V-Sb centre in our experiments. Most of the defects introduced by EBD and sputter deposition have also been observed after high-energy electron irradiation.…”
Section: Introductioncontrasting
confidence: 99%
“…The fact that the E-centre is not observed after sputter deposition in our system may imply that our sputter process does not introduce a sufficient number of single vacancies at and close to the surface that can diffuse into the Ge and combine with Sb ions to form V-Sb, as in the case of EBD. It should be realised that most of the damage that we observe after sputter deposition is caused by backscattered neutral Ar ions that, for the sputter conditions used here, have a maximum energy of approximately 700 eV of RF power [9]. From TRIM [14] modelling we have found that the range and straggle of these ions are 2.1 and 1.2 nm, respectively.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…Defects introduced in Ge during metallization processes have been investigated [11,26,27,28,29,30,31].…”
Section: Introductionmentioning
confidence: 99%